BRAND IMAGE TERHADAP AFFECTIVE LOYALTY DAN DAMPAKNYA TERHADAP WORD OF MOUTH - Rosyadah, Marisa Elma; Lukitaningsih, Ambar; Hutami, Lusia Tria Hatmanti (LPPM STIE Muhammadiah Bandung, 2022)
The formation of a Brand Image can affect the Affective Loyalty to use a product. Before buying a product, consumers will simply form a belief before finally making a choice of a product, then assessing whether the product is suitable and finally making a decision to make a purchase transaction. The sample method is accidental sampling. The questionnaires that were processed were 100. The findings show that brand image is influential positive effect on affective loyalty, affective loyalty has a positive effect on word of mouth brand image has a negative effect on word of mouth. Further results show that affective loyalty mediates brand image and word of mouth.